The Use of Modern Applications in English Language Learning - Godárová, Vanessa (Univerzita Pardubice, 2020)
This bachelor thesis deals with evaluation of modern language learning applications as tools for learning English, mainly from the point of view of motivation. In the theoretical part the concepts of motivation and learning are defined. Furthermore, the concepts are put into the context of mobile language learning. Subsequently, the mobile applications are described and divided based on their functions. Also, the criteria for evaluation of mobile learning applications as learning materials are presented. Finally, the motivational strategies are defined and put into the context of modern learning applications. In the practical part, two chosen applications are evaluated based on the findings from the theoretical part of the thesis.
Používání moderních aplikací při učení se anglickému jazyku
Keywords: motivace; mobilní učení; jazykové aplikace; komunikativní kompetence; motivation; mobile learning; language applications; communicative competence